(3Odjd GSJYeGd (BMicrosoft VISUAL BASIC /s - (3Ldhd, MejOs ((3GdLRGFQ(B: s (3OGQ GdSdGe(B, s, 2003)
1- (3GdeHGOF GdGSGSjI deMjW GdHQeLI ajRjGd HGRjc hGdCOhGJ GdJGHYI dg (B2-(3GdYedjGJ GdMSGHjI hGdLed GdTQWjI hGdMdbGJ GdJcQGQjI GdbhGFe heQHYGJ GdMhGQ (B3- (3GfTGA bhGYO GdHjGfGJ GdHQeLjI HdZI (BSQL(3hWHGYI GdJbGQjQ QSheGJ JhVMjIs
Keywords: Microsoft VISUAL BASIC